2009
DOI: 10.1177/0091270009337011
|View full text |Cite
|
Sign up to set email alerts
|

The Vytorin on Carotid Intima‐Media Thickness and Overall Arterial Rigidity (VYCTOR) Study

Abstract: This study assessed the effect of 3 lipid-lowering therapies on the reduction of the carotid intima-media thickness (IMT) in high-risk coronary Mexican patients. The study was a randomized, comparative, and open clinical trial. Ninety high-risk coronary patients were allocated to 3 groups: pravastatin 40 mg, simvastatin 40 mg, and simvastatin 20 mg and ezetimibe 10 mg initially. If the therapeutic goals were not attained (<100 mg/dL of low-density lipoprotein cholesterol [LDL-C] for type C and <70 mg for type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 64 publications
1
30
0
1
Order By: Relevance
“…In contrast to the ENHANCE study, some previous studies reported the beneficial effect of combination therapy with ezetimibe and a statin on carotid atherosclerosis, consistent with our results. 23,24) More recently, there have been several studies that supported the antiatherosclerotic effect of ezetimibe. Habara, et al reported that combination therapy with ezetimibe and fluvastatin increased the fibrous cap thickness of lipid-rich coronary plaque compared with fluvastatin alone in patients with stable CAD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the ENHANCE study, some previous studies reported the beneficial effect of combination therapy with ezetimibe and a statin on carotid atherosclerosis, consistent with our results. 23,24) More recently, there have been several studies that supported the antiatherosclerotic effect of ezetimibe. Habara, et al reported that combination therapy with ezetimibe and fluvastatin increased the fibrous cap thickness of lipid-rich coronary plaque compared with fluvastatin alone in patients with stable CAD.…”
Section: Discussionmentioning
confidence: 99%
“…4,[11][12][13][14][15][16][17] Similarly, significant reductions in cIMT and LDL-C lowering were observed in the Vytorin on Carotid-media Thickness and Overall Arterial Rigidity study (VYCTOR) with simvastatin 20 mg and ezetimibe 10 mg therapy. 23 However, in the Arterial Biology for the Investigation of the Treatment Effects of Reducing Cholesterol 6-HDL and LDL Treatment Strategies trial (ARBITER 6) in CHD/CHD risk patients on long-term statin therapy, extended-release niacin significantly reduced cIMT thickness, and no significant change was observed with ezetimibe. The minimal cIMT change with ezetimibe in ARBITER 6 was consistent with the aforementioned studies in patients with extensive prior statin therapy and/or relatively low baseline cIMT, including ENHANCE.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the results of large clinical trials assessing the effects of the combined treatment with these agents are not so clear-cut. The effect of ezetimibe-simvastatin combination treatment on the carotid intima-media thickness was found in patients at high cardiovascular risk [4], as well as in patients with type 2 diabetes and no prior cardiovascular events [5], but not in patients with ischaemic heart disease or its equivalent [6] nor in patients with familial hypercholesterolemia [7]. Moreover, although in patients with mild-to-moderate, asymptomatic aortic-valve stenosis, simvastatin-ezetimibe combination treatment reduced the incidence of ischaemic cardiovascular events, the treatment had no overall effect on the course of aorticvalve stenosis [8].…”
Section: Introductionmentioning
confidence: 99%